Antimicrobial Potential of Crude Extract of Curvularia lunata, an Endophytic Fungi Isolated from Cymbopogon caesius. (24th November 2015) - Avinash, K. S.; Ashwini, H. S.; Babu, H. N. Ramesh; Krishnamurthy, Y. L.
Abstract : Cymbopogon caesius grass is an aromatic tall grass species which grows in waste field and along the edges of crop fields in Karnataka. From this grass fungal endophytes were isolated on PDA medium and identified as Curvularia lunata . The fungus was cultured on Potato Dextrose broth for production of fungal metabolites. Ethyl acetate extract of the C. lunata was obtained by liquid-liquid partition of broth of endophyte and evaporation. Dried crude extract was tested for antimicrobial activity by agar well diffusion method. The extract showed antimicrobial nature against all the test pathogens. Crude extract of C. lunata is highly active against Staphylococcus aureus with the inhibition percentage of 92 and Candida albicans with 81 percent inhibition.